Common category organization in bilingual Spanish-English adults - Hough, Monica; Perara, Jackeline; Sencion, Giselle; Swartz, Maya (Journal of Monolingual and Bilingual Speech, 2024)
The purpose of the present study was to examine differences in categorization between Spanish and English in bilingual adults. Participants were asked to generate as many examples as possible within 2 minutes for four common categories. Number of items produced, and category structure relative to typicality for each category, was analyzed in 25 simultaneous Spanish-English bilingual participants between the ages of 18–65. Performance between the two languages was evaluated relative to several variables that may contribute to language use differences between languages in bilingual persons. Results revealed there were significant differences in the number of items produced in English versus Spanish for all four categories, with participants producing significantly more items in English than Spanish. There were no significant differences in mean typicality ratings between English and Spanish for three of the four categories. However, for the category ‘vegetables’, participant responses showed a remarkably lower mean typicality rating in English versus Spanish. Correlation analyses revealed negative relationships between education level and typicality data for both languages. However, age and time spent in the United States was significantly correlated, but only for Spanish data. Thus, the current findings support the idea that the way information is organized relative to categorization is individualized, linked to the bilingual individual’s language environment.